2021
DOI: 10.1111/jch.14220
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment, and control of hypertension in Nigeria in 1995 and 2020: A systematic analysis of current evidence

Abstract: Improved understanding of the current burden of hypertension, including awareness, treatment, and control, is needed to guide relevant preventative measures in Nigeria.A systematic search of studies on the epidemiology of hypertension in Nigeria, published on or after January 1990, was conducted. The authors employed randomeffects meta-analysis on extracted crude hypertension prevalence, and awareness, treatment, and control rates. Using a meta-regression model, overall hypertension cases in Nigeria in 1995 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 78 publications
(134 reference statements)
6
69
0
Order By: Relevance
“…This study's pooled estimate of prehypertension prevalence in Nigeria, 34% (95% CI: 30-40%), is close to but more precise than a recent meta-analysis in the country, which reported a prevalence of 30.9% (95% CI: 22.0-39.7%) (6). The difference in precision between the two meta-analyses can be explained by the difference in the number of studies and individuals included in each; our analysis includes a larger number of studies and individuals, which explains our estimate's higher precision.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This study's pooled estimate of prehypertension prevalence in Nigeria, 34% (95% CI: 30-40%), is close to but more precise than a recent meta-analysis in the country, which reported a prevalence of 30.9% (95% CI: 22.0-39.7%) (6). The difference in precision between the two meta-analyses can be explained by the difference in the number of studies and individuals included in each; our analysis includes a larger number of studies and individuals, which explains our estimate's higher precision.…”
Section: Discussionsupporting
confidence: 68%
“…The difference in precision between the two meta-analyses can be explained by the difference in the number of studies and individuals included in each; our analysis includes a larger number of studies and individuals, which explains our estimate's higher precision. It's worth noting that prehypertension and hypertension have nearly identical prevalence rates (6). This indicates that twothirds of adult Nigerians have high blood pressure and are at a high risk of acquiring end-stage cardiovascular events such as stroke, coronary heart disease, and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that about a third of hypertensives are unaware of their status. 5 , 6 Hence, every adult participant at the medical outreach programmes is screened for hypertension and diabetes mellitus. Also, every adult patient has a BP measurement at each clinic visit, irrespective of the clinical presentation.…”
Section: Primary Care Practice and Public Healthmentioning
confidence: 99%